Environmental Humanities in pre-service teachers' Education - Martín Ezpeleta, Antonio; Echegoyen Sanz, Yolanda (Journal of Education Culture and Society, 2018)
Aim: The aim of the reserch is to explore the possibility of integrating Sciences and Humanities in the Faculty of Education using Ecocriticism books and literary workshops with didactic activities of interdisciplinary nature.Methods: The experience was carried out with 100 students of the Faculty of Education of the University of Valencia from the subjects “Natural Sciences for teachers” and “Literary training for teachers”, where different didactic activities around two literary works, a novel and a short story, were proposed.Results: After the activities, the vast mayority of the students consider that Literature can help to learn Science. 41'7% of the students of “Literary training for teachers” and 62.5% of “Natural Sciences for teachers” consider the integration of Sciences and Humanities in class “very important”; and 55.6% and 29.2% “quite important”. More than 90% of the students said they were “very” or “quite” conscious of sustainability and environmental protection, although the percentages vary slightly between the two classes.Conclusion: With this study we have shown that Ecocriticism and Education are two interlinked concepts, in the same way that literature and society are. Using the socializing function of literature is when we can have greater educational performance in the current classrooms, because it allows the students to connect their reality with the texts. These ecocriticism works are a first-order didactic resource to raise awareness about environmental and sustainability problems in pre-service teachers that will transmit the message to their future students.